Intellectual Property Rights and Competition Policy - Mattias Ganslandt (Research Institute of Industrial Economics (IFN), 2007)
Intellectual property rights and competition policy are intimately related. In this paper I survey the economic literature analyzing the interaction between intellectual property law and competition law and how the boundary between these two policies is drawn in practice. Recognizing that intellectual property rights and competition law can interact in many different ways, the presentation focuses on several key issues. The economic literature on the interaction between competition law and intellectual property rights shows that these regulatory systems are consistent in terms of basic principles. Significant tensions exist, however, and it is difficult to balance IPR and competition law in practice. The significant differences in approach between the United States and the European Union simply reflect the underlying reality that efforts to achieve a sensible balance do not result in policy harmonization.
Keywords: K21; L41; O31; O34; 330; IPR; Competition Policy; Antitrust Policy; Cross-licensing; Refusal to License; Patent Pools; Tying; Patent Litigation; Immaterialgüterrechte; Wettbewerbsrecht; Wettbewerbspolitik; Konzentrationspolitik; Patent; Lizenz; EU-Staaten; USA